MORAL DALAM NOVEL â€œMEIN ONKEL FRANZâ€ KARYA ERICH KÃ„STNER - KURNIAWAN, ADE (IDENTITAET, 2016)
Moral to Rachels (2004: 35) is the problems to do something good or bad. Moral teaching is done in the framework of any kind, and is determined by the best reasons for doing so. In the novel, Erich Kästner life story also contains many moral messages that can be a lesson for the reader. Formulation of the problem in this research is: What is the mood in the novel "My uncle Franz" by Erich Kästner? The study specifically to describe the moral figures in the novel "My uncle Franz" by Erich Kastner. This research in the research descriptive kualtatif included. Moreover, in order to analyze the use of the theory of James Rachels. Theori "moral" according to Rachel in verwendba for Analisierung. Based on these Theori are the findings as; (1) The courage: Uncle Franz, Uncle Paul, Uncle Robert and Ida Augustin; (2) The generosity: Uncle Franz, Grandfather Augustin, Aunt Lina; (3) The Candid: Ida Augustin, Erich Kästner; (4) The reward: Uncle Franz, Ida Augustin, Augustin grandfather, aunt Lina, Tante Marie, and Dora; (5) The independence: Uncle Franz, Uncle Paul, Grandfather Augustin; (6) Humility: Uncle Franz, Ida Augustin, and Emil Kästner. The analytical method used is as follows: to read (1) and to understand the novel, (2) collect data quoted text with characterization methods, (3) the classification of Describe data in the form of words, sentences and phrases related to the behavior, moral good and bad, by the code the data, (4) describe the data, (5) take the conclusion that the results obtained by the analysis. And the results of this study consists of 6 moral details, 10 figures, and 19 written data. Keywords: morality, Roman, Kästner